Development of E-Modules in Applied Linguistics Learning Based on the Independent Curriculum with Local Wisdom Content in Bojonegoro - Nilna Indriana; Mas Tajuddin Ahmad (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
In the 21st century education demands integrating technology into learning to improve students' skills and readiness to meet the challenges of the digital era. The Industrial Revolution 4.0 and the concept of Society 5.0 encourage the use of Information and Communication Technology (ICT) in the Merdeka Learning curriculum, which aims to provide a more innovative and responsive learning experience in line with current developments. However, the implementation of technology in learning still faces various obstacles, including a lack of understanding of local wisdom in the curriculum content. In this context, it is important to develop a curriculum grounded in local wisdom to strengthen students' cultural identity and character. Bojonegoro has rich cultural potential, such as Jenogoroan painted batik, which can be introduced to younger generations through education. The lack of integration of local wisdom into university courses indicates the need for innovative approaches, such as the development of digital teaching materials in the form of e-modules. This research aims to develop e-modules in Applied Linguistics Learning Based on the Merdeka Curriculum with Bojonegoro Local Wisdom Content. With an approach based on technology and local culture. With the development of this e-module, it is hoped that students will gain a better understanding of the relationship between language and local culture, while simultaneously enhancing their academic competency in applied linguistics.“Furthermore, integrating technology into learning can increase motivation to learn and prepare students to face global challenges while preserving their cultural identity. The product will be produced through R&D research using the ADDIE design. ADDIE consists of five stages: analysis, design, development, implementation, and evaluation.